1994
DOI: 10.1002/aja.1002000107
|View full text |Cite
|
Sign up to set email alerts
|

Barrier inhibition of a temporal neuraxial influence on early chick somitic myogenesis

Abstract: Skeletal myogenesis in the chick embryo first occurs in the somite. Somites are transient, paired mesodermal structures adjacent to the neural tube. Somites form from the segmental plate mesenchyme at approximately 90-min intervals. We identify somitic myogenic cells by using confocal microscopy to detect the muscle specific intermediate filament protein, desmin, in whole mount chick embryo preparations. The appearance of desmin in somitic cells does not occur at a constant interval after the somite has formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Cells isolated from UPM or somites I-V did not give rise to differentiated cells under any of the conditions tested, even when plated on primary embryonic cells, where some single mesodermal cells must come into close contact with neuronal or notochordal cells. This suggests that at low density, single mesodermal cells fail to respond to inductive signals from axial structures (5)(6)(7)(8)(9)(10). In contrast to these results, cells isolated from somites VI-X and from FLB differentiated at very low frequency on collagen but gave rise to many muscle clones on feeder layers.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Cells isolated from UPM or somites I-V did not give rise to differentiated cells under any of the conditions tested, even when plated on primary embryonic cells, where some single mesodermal cells must come into close contact with neuronal or notochordal cells. This suggests that at low density, single mesodermal cells fail to respond to inductive signals from axial structures (5)(6)(7)(8)(9)(10). In contrast to these results, cells isolated from somites VI-X and from FLB differentiated at very low frequency on collagen but gave rise to many muscle clones on feeder layers.…”
Section: Resultsmentioning
confidence: 84%
“…The timing of this phenomenon is roughly comparable to the timing of the community effect; i.e. only UPM and newly formed somites require axial induction to undergo myogenesis, whereas more mature somites differentiate independently of this influence (9,10). However, since at present it is not possible to identify with certainty possible axial inducers (candidates include neural crest, neurons, and notochord) in reaggregated pellets and undissociated clusters, we repeated the experiments using either isolated somites and UPM or trunk segments, which are likely to contain these potential inducers.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding led to the assumption that the naive paraxial mesoderm is specified for the myogenic lineage by inductive influences from neighboring tissues. Ablation experiments have identified three structures that are required for myogenesis: the neural tube (Christ et al 1992, Rong et al 1992, Borman and Yorde 1994, Buffinger and Stockdale 1994, Cossu et al 1996, the notochord-floor plate complex (Buffinger andStockdale 1994, Stern and, and the dorsal ectoderm (Christ et al 1972, Cossu et al 1996. In molecular terms, it appears that a delicately balanced level of both Shh from the notochord and Wnts from the dorsal neural tube and the ectoderm acts to elicit myogenesis, while high levels of Shh or Wnt alone lead to sclerotomal or nonmyogenic dermomyotomal differentiation, respectively .…”
Section: Initiation Of Myogenesismentioning
confidence: 97%
“…Studies on avian mesoderm patterning showed that specification of individual somites along their R-C extent is a somite-intrinsic property arising already prior to segmentation; by contrast, dorsoventral somite patterning, as well as the commitment of the medial somite to a myogenic fate, seem to be induced by signals from adjacent structures (Borman and Yorde, 1994;Buffinger and Stockdale, 1994;Dietrich et al, 1997;Kenny Mobbs and Thorogood, 1987;Münsterberg et al, 1995;Münsterberg and Lassar, 1995;Pownall et al, 1996;Rong et al, 1992;Stern et al, 1995;Vivarelli and Cossu, 1986) (for reviews, see Bothe et al, 2007;Christ et al, 2007;Christ and Scaal, 2008). Our results stemming from M-L somite inversions, performed prior to the onset of MyoD or Myf5 expression, are consistent with the axial structures inducing the medial somite to generate pioneer myoblasts.…”
Section: Discussionmentioning
confidence: 99%